Mіnі-rеvіеw: Advаnсеs іn thе sуnthеsіs аnd bіоlоgісаl асtіvіtу оf bеnzоfurохаn аnd furохаn dеrіvаtіvеs - Zhаnаkоv, Mukhtar; Zhatkanbayeva, Zhanna; Сhugunоvа, Elena; Akylbekov, Nurgali; Zhаtkаnbауеv, Yerlan (Chemical Bulletin of Kazakh National University, 2025)
Benzofuroxan and furoxan derivatives are heterocyclic compounds well known for their ability to act as nitric oxide (NO) donors. Due to their NO-releasing properties, these compounds have attracted considerable attention for their antimicrobial, antiviral, and antitumor activities. Their potential use in treating cardiovascular, gastrointestinal, and neurodegenerative disorders further underscores their pharmacological relevance. Given the increasing research interest in these compounds, there is a need to consolidate recent findings related to their chemical properties and biological potential. This mini-review aims to provide an up-to-date overview of the synthetic strategies and bioactivities of benzofuroxan and furoxan derivatives. Rather than focusing on ring synthesis, this review highlights the reactivity of side-chain functional groups and the design of hybrid molecules. Representative examples of drug-like compounds are discussed, along with their biological profiles. The review also explores emerging directions in the development of novel NO donors based on these frameworks with improved pharmaceutical efficacy and controlled NO release.